Effects of Aspergillus oryzae on ruminal fermentation of an alfalfa hay:concentrate diet using the rumen simulation technique (Rusitec) - Sosa, Areadne; Saro, Cristina; Mateos, I.; Díaz, A.; Galindo, Juana; Carro, María D.; Ranilla, María (Cuban Journal of Agricultural Science, 2020)
Direct-fed microbial products have been shown to modify ruminal fermentation parameters and to have beneficial effects on ruminant performance. The aim of this study was to evaluate the effect of Aspergillus oryzae on ruminal fermentation of a 65:35 alfalfa hay:concentrate diet in continuous fermentation system Rusitec. Four fermenters corresponded to the control and four received 50 mg of A. oryzae lyophilized culture which was mixed with feed. Treatment with A. oryzae increase (p < 0.001 to p = 0.039) acetate, total short chain fatty acids (SCFA), minor SCFA production and acetate:propionate (Ac:Pr) ratio. A. oryzae addition decreased (p < 0.001) pH values and increased (p < 0.001) ammonia-N concentration. There were no differences among treatments in methane production (p = 0.230). The inclusion of A. oryzae did not affect (p = 0.386 to p = 0.865) the dry matter and fiber disappearance. Rumen fluid from A. oryzae fermenters did not affect (p=0.465 to p=0.938) gas production neither (p = 0.131 to p = 0.942) total SCFA from pure substrates. The increase of acetate, minor SCFA and total SCFA production indicate that A. oryzae strain stimulated rumen fermentation of a 65:35 alfalfa hay:concentrate diet in continuous fermentation system Rusitec. Keywords: continuous fermenters, direct-fed microbial, fiber degradability, volatile fatty acids